2009
DOI: 10.1161/circresaha.109.198572
|View full text |Cite
|
Sign up to set email alerts
|

Using Lidocaine and Benzocaine to Link Sodium Channel Molecular Conformations to State-Dependent Antiarrhythmic Drug Affinity

Abstract: A subset share characteristics that make them effective as antiarrhythmic drugs, ie, they exhibit high affinity, use-dependent block of Na current (I Na ) at high heart rates. Despite extensive study, there remains uncertainty regarding how observed block relates to specific drug-channel conformations. Several vocabularies have emerged to describe block, which in general, have their basis in kinetic models of Na channel gating and assume preferential binding to one or more states that produce no 1 or altered 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 39 publications
7
74
0
Order By: Relevance
“…Consistent with earlier studies, we found almost no use-dependent inhibition by benzocaine 20,25,33,39 ( Supplementary Fig. S5), suggesting that a protonated amine is necessary for use-dependent inhibition.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with earlier studies, we found almost no use-dependent inhibition by benzocaine 20,25,33,39 ( Supplementary Fig. S5), suggesting that a protonated amine is necessary for use-dependent inhibition.…”
Section: Resultssupporting
confidence: 92%
“…It is generally appreciated that sodium channel inhibitor action involves a number of different mechanisms 12 including pore block 13 , electrostatic interactions between the cationic charge on the drug and sodium ions at the selectivity filter 14,15 , stabilization of either fast or slow non-conducting states of the channel 16,17 , gating charge immobilization [18][19][20] , and targeted uncoupling of channel gating from voltage-sensing 21 . Previous studies have shown that site-directed mutation of two strictly conserved aromatic residues in transmembrane segment 6 (S6) of the fourth sodium channel domain (DIV), Phe1760 and Tyr1767 in Na v 1.5, can virtually abolish channel inhibition by all classes of anti-arrhythmic drugs 12,[22][23][24] .…”
mentioning
confidence: 99%
“…Residues F1774 and Y1781 of DIV (and residues in DI and DIII) of eukaryotic sodium channels have been identified as important for binding channel-blocker compounds (7)(8)(9)(10)(16)(17)(18) and use-dependence drug-binding (8,17). The residues in DIV correspond to residues T207 and F214 in NavMs (Figs.…”
Section: Significancementioning
confidence: 99%
“…Although there are as yet no crystal structures of eukaryotic sodium channels, crystal structures of several prokaryotic sodium channels in different conformational states have been determined, including ones with closed (2), partially (3) and fully (4) open pores, and two potentially inactivated forms (5,6). Mutations in human sodium channels (hNa v s) have been linked to channelopathies such as epilepsy, cardiac arrhythmia, and chronic pain syndromes; consequently sodium channel blockers have been developed as anticonvulsant, antiarrhythmic, and local anesthetic drugs (7)(8)(9)(10). Several eukaryotic calcium channel blocker drugs have previously been found to bind and block prokaryotic sodium channels (11)(12)(13).…”
mentioning
confidence: 99%
“…state [25] . The latter type of inactivation only occurs at very high concentrations and is therefore considered to be a low-affi nity block, so this was not a concern in the current residues within S6, such as L1280 and P1759 [10] .…”
Section: Discussionmentioning
confidence: 99%